Real exchange rate and terms of trade: Some empirical evidence in Malaysia, Singapore, and Thailand - Wong, Hock Tsen (Universiti Utara Malaysia, 2009)
This study examined the relationship between real exchange rate and terms of trade in Malaysia, Singapore, and Thailand in two cases, namely a three-variable case and a four-variable case. The results of co-integration tests showed that there is long-run relationships among real exchange rate, terms of trade, and relative demand for Malaysia. Moreover, there is long-run relationship among real exchange rate, terms of trade, relative demand, and relative real interest rate for Malaysia and Thailand. The results of Granger causality showed that real exchange rate does not Granger cause terms of trade, however the result is mixed for Thailand. The contribution of terms of trade and relative demand to real exchange rate is mixed and small. Generally, the contribution of terms of trade to real exchange rate is greater than the contribution of relative demand in Singapore. For Thailand, relative demand is more important than terms of trade in the determination of real exchange rate. For Malaysia, the results are mixed.